Cohabiting a textualized world: Elbow room and adivasi resurgence - Hembrom, Ruby (Modern Asian Studies)
Stories matter$1 (Bwriting them down matters. For indigenous (Adivasi) peoples from oral traditions, literature has become a way to maintain culture and keep it alive. This article too is a story$1 (Ban investigative one$1 (Bquestioning and vocalizing the challenges we encounter in trying to articulate our realities and histories in a form that is new to us, one that we've been denied as a practice and one we are not believed we are entitled to use. Mainstream cultures have side-lined, overshadowed, and subjugated our knowledge systems, placing us in structures we have to traverse, and within which we have to exist, which is possible only by internalizing and mirroring others' or mainstream ways and languages to gain legitimacy as peoples or, worse, being branded and judged by their versions of narratives of us. This article plots the course of Adivasi histories and narratives enduring, outlasting, or being demolished by dislocation and dispossession, by dominant languages and cultures, and how both writing and orality are practices of both resistance and resurgence.- Reproduced s
Keywords: Adivasi, Tribal, Indigenous, orality, Writing, Publishing